ANALISIS TATA KELOLA KAPASITAS LAYANAN TEKNOLOGI INFORMASI PERUSAHAAN ASURANSI SOSIAL MENGGUNAKAN STANDAR ISO 20000:1-2018 - Anggraeni Ridwan; Agus Suwinto (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Abstract : Social insurance company has mission to protect all people, avoid the risk of social life, so social insurance company must provide public services that are easy to use. To provide fast, accurate, and information, ensuring the reliability of information technology service capacity governance is very important. Social insurance company needs period of preparation for development towards vision (Good Governance, Risk Management, and Compliance) in service excellence, taking into account the governance of information technology service capacity which is important factor for Social Insurance Company. ISO is a standard-setting body that provides world-class specifications for variety of things, from products, services and systems, to ensure quality, safety and efficiency. Therefore, this paper provides an overview the implementation of ISO 20000-1: 2018 standards for Information Technology Services Capacity Management with standardization clauses for social insurance company and review information technology service capacity governance standards as considerations and proposals to Social Insurance Company